Wholesale and retail market prices of commodities : April-June, 1980 - Anambra State. Ministry of Finance and Economic Development; Ministry of Finance and Economic Development (Enugu : Ministry of Finance and Economic Development Statistics Division, 1980)
This is a publication of the Ministry of Finance and Economic Development Statistics Division, Anambra State of Nigeria, It provides wholesale and retail market prices of commodities in the state for the period April-June, 1980.
lje 04/03/2019
Arch
Keywords: Prices; Commerce; Nigeria